Response of NaCl stress to morphology and content of phenolic compounds, flavonoids, and antioxidant activity in clove seeds (Syzycum aromaticum.L) - Bagus Tripama; Tri Agus Siswoyo; Parawita Dewanti; Sigit Soeparjono (Jurnal Penelitian Pertanian Terapan, 2023)
NaCl stress in plants affects various physiological and biochemical processes that result in reduced biomass production. This study aims to determine the aspects of morphological and physiological changes of plants with indications of the induction of secondary metabolism in survival, which is indicated by an indication of an increase in bioactive compounds, including phenolic compounds, flavonoids, single oxygen (O2), hydroxyl radicals (OH-), radicals ( O-2), and superoxide. The clove seed pot experiment under NaCl stress used a randomized block design with three replications. Data are presented as mean ± standard deviation. The significance of the difference between the mean values was tested by analysis of variance, if there was a significant effect, then Duncan Multiple Range Test (DMRT). The results of the NaCl stress study on clove seeds showed fluctuating phenolic and flavonoid content, almost all NaCl treatment with the optimum plant value obtained at a NaCl concentration of 200 mM, with a content of (1.18μg GAE/g) and flavonoids (0.158 g QE/g) ( 1.18μg GAE/g). The antioxidant activity of DPPH, Hydroxyl activity, Superoxide is also affected by the concentration of NaCl